Uncommon presentation of duodenal gastrointestinal stromal tumor as large paraduodenal cyst: case report - Kerkar, Prashant B.; Sabireen; Pohekar, Monika; Mohanty, Mahesh (International Surgery Journal, 2024)
Gastrointestinal stromal tumors (GISTs) are rare solid mesenchymal neoplasms. Small bowel GISTs have predominantly an outward growth and multifocal when associated with neurofibromatosis-1 (NF-1). When the duodenum is involved, lesions may be more challenging if growing towards the pancreas. Their prevalence is unknown, and diagnosis is usually incidental. Owing to the complex anatomy of the duodenum and pancreatic head, GISTs can be misdiagnosed as pancreatic head tumors, however they presenting as cyst is very rare. Literature shows very few reported cases of cystic GISTS, all arising from the stomach or pancreas where they have been mistaken for pseudocysts or even a mucinous cystadenocarcinoma of the pancreas and only one case of duodenal GIST presenting as cyst has been reported so far. Here, we report a case where investigations including radiology and upper gastrointestinal endoscopy suggested it to be a paraduodenal cyst, but histopathological examination of the specimen resulted in an unexpected diagnosis of GIST. We concluded that non-invasive imaging like CT, MRI, EUS and whenever possible FNA are important for the diagnosis and treatment of GISTs. Surgical resection with clear margin is the desired treatment for a localised duodenal GIST. Also, the feasibility of limited resections such as duodenectomy without pancreatic/ampullary involvement as in our case report where we preserved the pancreas reduces the morbidity and complications associated with extensive surgeries like pancreaticoduodenectomy. Also, Imatinib is an effective therapeutic agent with a remarkable response and prolonged survival.